Technology based learning analysis of CBCS model at KKU - Case study of College of Computer Science King Khalid University, Saudi Arabia - Clementking, A; Muhammad, AbdulHafeez; Shah, Asadullah; Ahmad, Farooq (Kassel University Press, 2013)
The higher education frame works are attempted to develop the human capital of the country thinking of the next generation technology. The Kingdom of Saudi Arabia is prioritized the higher education sector is one among the segment in current scenario. The establishment of new universities and the business schools are evidence that the Kingdom of Saudi Arabia is providing higher education with the Islamic culture and values to build up the upcoming young generation. While providing the higher education model, mostly focused on the four sectors namely Islamic culture and values, basic science for life enhancement, higher education for technology and prepare the potential young youth for employment to buildup the human resource of the country. As part of the national mission and the vision of the country, the educations sectors are distributed the higher education frame work as Choice Based Credit System (CBCS) curriculum into these above stated four sectors. The study is made to analysis the Higher Education frame work of College of Computer Science curriculum, King Khalid University, Abha, Kingdom of Saudi Arabia. It evaluates the learner’s suitability potential to meet the enhancement of higher education in the same major subject and Employability in the specified filed with Islamic culture and values.